Metabolism-Driven High-Throughput Cancer Identification with GLUT5-Specific Molecular Probes - Srinivas Kannan (Biosensors, 2018)
Point-of-care applications rely on biomedical sensors to enable rapid detection with high sensitivity and selectivity. Despite advances in sensor development, there are challenges in cancer diagnostics. Detection of biomarkers, cell receptors, circulating tumor cells, gene identification, and fluorescent tagging are time-consuming due to the sample preparation and response time involved. Here, we present a novel approach to target the enhanced metabolism in breast cancers for rapid detection using fluorescent imaging. Fluorescent analogs of fructose target the fructose-specific transporter GLUT5 in breast cancers and have limited to no response from normal cells. These analogs demonstrate a marked difference in adenocarcinoma and premalignant cells leading to a novel detection approach. The vastly different uptake kinetics of the analogs yields two unique signatures for each cell type. We used normal breast cells MCF10A, adenocarcinoma cells MCF7, and premalignant cells MCF10AneoT, with hepatocellular carcinoma cells HepG2 as the negative control. Our data indicated that MCF10AneoT and MCF7 cells had an observable difference in response to only one of the analogs. The response, observed as fluorescence intensity, leads to a two-point assessment of the cells in any sample. Since the treatment time is 10 min, there is potential for use in rapid on-site high-throughput diagnostics.